The Effect of Using Different Raw Materials on the Characteristics of Vegetable Floss - Mirratunnisya Mirratunnisya; Putri Fara Dilla; Repka Natalia; Iffah Muflihati (Universitas Darussalam Gontor, 2021)
Flossis a food that is generally made from meat, but flosscan also be developed from local food ingredients that have fiber-like meat such as kluwih, breadfruit,and jackfruit. Making floss from local food can increase food diversification and its economicvalue. The purpose of this study was to determine the sensory and chemical characteristics of artificial flosses fromkluwih, breadfruit,and jackfruit. Thisresearch used a completely randomized design with 3 typesof the raw materials:kluwih, breadfruit,and jackfruit. The result of the water content test showed an average value of 3.47-3.65%. The results should that the floss from kluwih tended to be preferred by the panelists. The treatment of the use of different types of materials showed significantly different effects on moisture content, hedonicvalueand color ofthe vegetable floss